دور أخلاقيات المعلومة المحاسبية في تحقيق الكفاءة المعلوماتية لأسواق الأوراق المالية ـ دراسة تطبيقية على مستوى بورصة الجزائرـ - نورالدين, أ / بهلول (Sciences humaines, 2016)
تهدف هذه الدراسة الى بيان دور المعلومة المحاسبية المنتجة            من المؤسسات الوطنية المساهمة       في تطوير وتحقيق كفاءة سوق الأوراق المالية الجزائرية، وذلك من خلال قياس درجة التغير والتوقيت اللازم في أسعار أسهم المؤسسات المساهمة في البورصة عند إيداع تقاريرها السنوية لدى إدارة البورصة، و خلصت الدراسة         الى مجموعة من النتائج أهمها المستوى الضعيف للكفاءة التي يتميز بها سوق الأوراق المالية الجزائري والذي يعزى الى طرق التمويل المتبعة من قبل المؤسسة الجزائرية من جهة وثقافة المستثمر الجزائري من جهة ثانية. الكلمات المفتاحية: أخلاقيات العمل المحاسبي، المعلومة المحاسبية، كفاءة سوق الأوراق المالية.     This research has focused on the role of accounting information produced from national institutions that contribute to the development and achievement of the efficiency of the Algerian stock market, by measuring the degree of change and the time required in the price of stock of institutions contributing to the stock market, when they deposit their annual reports. Eventually, this study found many important results one of them is the low level of efficiency which  characterized the Algerian stock market , which is attributed on one hand to the financial methods of the Algerian institutions and on the other hand to the culture of the Algerian investor. Key Words: Accountancy Ethics, accounting information, the efficiency stock market.